Aberrant PTEN, PIK3CA, pMAPK, and TP53 expression in human scalp and face angiosarcoma. Issue 30 (30th July 2021) - Wan, Huiying; Zhang, Dingding; Hu, Weimin; Xie, Zhen; Du, Qiu; Xia, Qiongrong; Wen, Taishen; Jia, Haiping
Abstract : Abstract: Angiosarcoma is a rare, highly aggressive malignant tumor originating from endothelial cells that line the lumen of blood or lymphatic vessels. The molecular mechanisms of scalp and face angiosarcoma still need to be elucidated. This study aimed to investigate the expression of phosphatase and tensin homolog (PTEN), phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), phosphorylated mitogen-activated kinase-like protein (pMAPK), and tumor protein p53 (TP53) in scalp and face angiosarcoma and to assess tumor tissue apoptosis. The expression and intracellular distribution of PTEN, PIK3CA, pMAPK, and TP53 proteins in 21 specimens of human scalp and face angiosarcoma and 16 specimens of human benign hemangioma were evaluated using immunohistochemistry. Tumor cell apoptosis was assessed by terminal deoxyribonucleotide transferase-mediated dUTP nick end-labeling staining. Significantly lower PTEN but higher PIK3CA, pMAPK, and TP53 immunostaining were detected in the angiosarcoma specimens than in the benign hemangioma specimens( P < .01). The angiosarcoma tissues exhibited significantly higher apoptosis indices than the benign hemangioma tissues ( P < .01). The positive expression rates of PIK3CA, pMAPK, and TP53 were correlated with the degree of tumor differentiation in the human scalp and face angiosarcoma. The PI3K, MAPK, and TP53 pathways might be involved in angiosarcoma tumorigenesis in humans and may serve as therapeutic targets for the effective treatment of this malignancy.